Public awareness, concerns and attitudes towards energy transition in Kentucky - Sydney Oluoch; Nirmal Pandit; Leticia Munoz Revelo; Cecelia Harner (Renewable and Sustainable Energy Transition)
Kentucky’s coal industry has faced a sharp decline due to global concerns about climate change, the environmental impact of coal extraction, diminishing coal deposits, environmental regulations, expansion of renewables, and competitive natural gas prices. This downturn has significantly impacted the state’s economy, resulting in job losses and economic instability. This study explores three key factors of Kentucky’s energy transition through a statewide survey of 675 residents from 28 mining counties and 89 non-mining counties. We assess public awareness of energy transition-related terms, environmental justice concerns, and attitudes towards energy transition. Our results show that Kentucky residents have a higher awareness of commonly recognized terms such as ‘Global warming,’ ‘Climate change, ‘ and ‘Energy efficiency.’ The most common environmental justice concerns reported were access to energy, flooding, and air pollution. Reduction in electricity costs emerged as the factor with the strongest associations, followed by improving the economy, replacing historical and cultural values, and addressing climate change. Overall, the study offers critical insights into Kentucky’s energy transition, highlighting key areas for consideration in policy making and public engagement.